ASAS PACTA SUNT SERVANDA TERHADAP TINDAKAN GENOSIDA PALESTINA DALAM PERTANGGUNGJAWABAN PIDANA INTERNATIONAL - Maulani, Yayu; Dasuki, Dasuki; Zenno Januarsyah, Putra (Civis : Jurnal Ilmiah Ilmu Sosial dan Pendidikan, 2025)
The most significant subject of international law can be seen in a state building relationships with other states that are in line with international regulations. On the other hand, conflicts caused by differences in interests are not uncommon in relations between subjects of international law, especially states. They cannot always be resolved through peaceful settlement. Genocide is a deliberate act to erase or eliminate all or part of a national, racial, ethnic, or religious group. This occurs through the killing of members of the group, the infliction of severe physical or mental suffering, the creation of living conditions that cause bodily harm to some or all of the group, the prevention of childbirth, and the forced displacement of children. This research is normative juridical, which means that it focuses on the application of various principles or rules in positive law. The researcher used three approaches: International Instrument Approach, Conceptual Approach, and Case Approach. Whether International criminal liability can prosecute Palestinian perpetrators of genocide for violations of international treaties prohibiting genocide based on the principle of pacta sunt servanda Moreover, how the principle of pacta sunt servanda can be used when Palestine is not involved in international treaties prohibiting genocide